Adipose invariant natural killer T cells. Issue 3 (July 2014) - Lynch, Lydia
Summary Adipose tissue is a dynamic organ that makes up a substantial proportion of the body; in severe obesity it can account for 50% of body mass. Details of the unique immune system resident in human and murine adipose tissue are only recently emerging, and so it has remained a largely unexplored and unappreciated immune site until now. Adipose tissue harbours a unique collection of immune cells, which often display unusual functions compared with their counterparts elsewhere in the body. These resident immune cells are key to maintaining tissue and immune homeostasis, yet in obesity their chronic aberrant stimulation can contribute to the inflammation and pathogenesis associated with obesity. Anti‐inflammatory adipose‐resident lymphocytes are often depleted in obesity, whereas pro‐inflammatory immune cells accumulate, leading to an overall inflammatory state, which is a key step in the development of obesity‐induced metabolic disease. A good example is invariant natural killer T (iNKT) cells, which make up a large proportion of lymphocytes in human and murine adipose tissue. Here, they are unusually poised to produce anti‐inflammatory or regulatory cytokines, however in obesity, iNKT cells are greatly reduced. As iNKT cells are potent transactivaors of other immune cells, and can act as a bridge between innate and adaptive immunity, their loss in obesity represents the loss of a major regulatory population. Restoring iNKT cells, or activating them in obese mice leads to improved glucose handling, insulin sensitivity, and even weight loss, and hence represents an exciting therapeutic avenue to be explored for restoring homeostasis in obese adipose tissue.